Fabrication of a self-assembled honeycomb nanofibrous scaffold to guide endothelial morphogenesis. (7th July 2020) - Yao, Tianyu; Wieringa, Paul Andrew; Chen, Honglin; Amit, Chandrakar; Samal, Pinak; Giselbrecht, Stefan; Baker, Matthew B; Moroni, Lorenzo
Abstract: Controlling angiogenesis within tissue engineered constructs remains a critical challenge, especially with regard to the guidance of pre-vascular network formation. Here, we aimed to regulate angiogenesis on a self-assembled honeycomb nanofibrous scaffold. Scaffolds with honeycombs patterns have several desirable properties for tissue engineering, including large surface area, high structural stability and good permeability. Furthermore, the honeycomb pattern resembles early vascular network formation. The self-assembly electrospinning approach to honeycomb scaffolds is a technically simple, rapid, and direct way to realize selective deposition of nanofibers. To evaluate cell compatibility, spreading, proliferation and tube formation, human umbilical vein endothelial cells (HUVECs) were cultured on honeycomb scaffolds, as well as on random scaffolds for comparison. The optimized honeycomb nanofibrous scaffolds were observed to better support cell proliferation and network formation, which can facilitate angiogenesis. Moreover, HUVECs cultured on the honeycomb scaffolds were observed to reorganize their cell bodies into tube-like structures containing a central lumen, while this was not observed on random scaffolds. This work has shown that the angiogenic response can be guided by honeycomb scaffolds, allowing improved early HUVECs organization. The guided organization via honeycomb scaffolds can be utilized for tissue engineering applications that require the formation of microvascular networks.